2005
DOI: 10.1074/jbc.m504597200
|View full text |Cite
|
Sign up to set email alerts
|

Cog1p Plays a Central Role in the Organization of the Yeast Conserved Oligomeric Golgi Complex

Abstract: The conserved oligomeric Golgi (COG) complex is an evolutionarily conserved peripheral membrane oligomeric protein complex that is involved in intra-Golgi protein trafficking. The COG complex is composed of eight subunits that are located in two lobes; Lobe A contains COG1-4, and Lobe B is composed of COG5-8. Both in vivo and in vitro protein-protein interaction techniques were applied to characterize interactions between individual COG subunits. In vitro assays revealed binary interactions between Cog2p and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 53 publications
7
99
1
Order By: Relevance
“…Previous studies suggest that Cog6 interacts with a Cog5-Cog7 complex to form the structural core of lobe B (22,23,31,32). Consistent with this model, we found that bacterial coexpression of full-length K. lactis Cog5, Cog6, and Cog7 yielded a stable, monodisperse complex ( Structural Basis of the Cog5-Cog7 Interaction.…”
Section: Significancesupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies suggest that Cog6 interacts with a Cog5-Cog7 complex to form the structural core of lobe B (22,23,31,32). Consistent with this model, we found that bacterial coexpression of full-length K. lactis Cog5, Cog6, and Cog7 yielded a stable, monodisperse complex ( Structural Basis of the Cog5-Cog7 Interaction.…”
Section: Significancesupporting
confidence: 75%
“…1073/pnas.1414829111/-/DCSupplemental. cerevisiae Cog5 and Cog7 form an especially stable binary complex (22). Similarly, comprehensive in vitro cotranslation/coimmunoprecipitation experiments revealed that, among the eight human COG subunits, COG5 and COG7 were unusual in their ability to form a stable binary complex (23).…”
Section: Significancementioning
confidence: 99%
“…Despite progress in characterizing the structures of individual COG/Dsl1p/exocyst subunits, relatively little is known about how the subunits within each complex interact with one another (32,(34)(35)(36). One exception is the Dsl1p and Tip20p subunits of the Dsl1p complex, which were recently shown to interact via N-terminal ␣-helices (20).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, the virtually complete Cog1 deficiency affects the stability of all lobe B subunits while not dramatically affecting Cog2, -3, and -4 levels (7,9,13). In yeast, the interaction of the Cog2-4 subunits with the Cog5-8 subunits is disrupted in either Cog1-deficient cells or cells expressing Cog1 with an 80-residue truncation at the N terminus (33). We found that the truncated C terminus of Cog1 in our patient's cells was associated with an instability in Cog2-4 and Cog8, but not the Cog5-7 subcomplex.…”
Section: Effects Of Truncated Cog1 On Golgi Matrix Proteins and Enzymesmentioning
confidence: 99%
“…This relationship may be due to the possible role of COG in controlling intraGolgi trafficking of some resident Golgi proteins (e.g., COPI-dependent retrograde trafficking) (32). The analysis of human COG subunit mutations from CDG patients, together with mammalian somatic cell mutants, yeast mutants, and RNA interference knockdown studies (9,12,33), should help define the precise mechanism by which COG controls the structure and function of the Golgi apparatus.…”
Section: Effects Of Truncated Cog1 On Golgi Matrix Proteins and Enzymesmentioning
confidence: 99%